1993
DOI: 10.1002/nt.2620010508
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of various classes of anti‐emetics in preventing deoxynivalenol‐induced vomiting in swine

Abstract: The Fusarium mycotoxin deoxynivalenol (DON) is a potent emetic agent. While the basic mechanisms which invoke and mediate emesis are still poorly understood, various neurotransmitters appear to be involved. The action of these transmitters can be blocked by various receptor-specific antagonists. The current study investigated the efficacy of several classes of receptor antagonists to block the emetic effect of DON. Following anti-emetic pretreatment, pigs were administered the toxin (i.v., 80 micrograms/kg, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…The present data agree with Etienne and Waché (2008), who cited a 4.6% decrease in ADFI for every 1 mg/kg of DON in the diet, and Frobose et al (2015), who described the feed intake suppression pattern as being the most marked during the initial exposure period and lessening over time. The anorexic effects of DON are most frequently attributed to changes in the metabolism and concentration of brain neurotransmitters such as serotonin in cerebrospinal fluid (Prelusky and Trenholm, 1993;Prelusky, 1994), causing delayed gastric emptying and decreasing small-intestinal motility (Rotter et al, 1996). Moreover, pigs develop conditioned taste aversion to DON-contaminated feedstuffs (Ossenkopp et al, 1994), which is consistent with observations of feed refusal and general anxiety in pigs fed DON (Bergsjo et al, 1993;Dänicke et al, 2004a).…”
Section: Growth Experimentssupporting
confidence: 65%
“…The present data agree with Etienne and Waché (2008), who cited a 4.6% decrease in ADFI for every 1 mg/kg of DON in the diet, and Frobose et al (2015), who described the feed intake suppression pattern as being the most marked during the initial exposure period and lessening over time. The anorexic effects of DON are most frequently attributed to changes in the metabolism and concentration of brain neurotransmitters such as serotonin in cerebrospinal fluid (Prelusky and Trenholm, 1993;Prelusky, 1994), causing delayed gastric emptying and decreasing small-intestinal motility (Rotter et al, 1996). Moreover, pigs develop conditioned taste aversion to DON-contaminated feedstuffs (Ossenkopp et al, 1994), which is consistent with observations of feed refusal and general anxiety in pigs fed DON (Bergsjo et al, 1993;Dänicke et al, 2004a).…”
Section: Growth Experimentssupporting
confidence: 65%
“…This is because the vomiting center in the brain is stimulated when either the receptors in the periphery (gastrointestinal tract) or in the blood are activated by the presence of toxins (Horn, 2008; Prelusky and Trenholm, 1993). Studies have shown that trichothecenes cause gastroenteritis (Pestka, 2010), which activates the enterochromaffin cells in the epithelium to release 5-hydroxytryptamine (5-HT) or serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that trichothecenes cause gastroenteritis (Pestka, 2010), which activates the enterochromaffin cells in the epithelium to release 5-hydroxytryptamine (5-HT) or serotonin. The 5-HT neurotransmitter sends signals to the brain vomiting center to induce vomiting (Prelusky and Trenholm, 1993). Likewise, introduction of toxins into the blood by IP dosing or absorption from the gut into the systemic circulation can stimulate the vomiting center via direct activation of 5-HT 3 receptors in the chemoreceptor trigger zone (CTZ) in the brain (Becker, 2010; Dietrich et al, 2015; Kovac, 2016; Horn, 2008; Lang, 1999; Prelusky and Trenholm, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although these specific toxins have not been as extensively studied as the trichothecenes deoxynivalenol and T-2 toxin, their mechanism of toxicity is thought to be very similar or the same. High-dose exposure to deoxynivalenol causes emesis and myocardial and gastrointestinal hemorrhages; lower exposures cause damage to the immune system, affect the appetite center of the brain, and alter neurotransmitter levels (24)(25)(26)(27). Primarily because of the immunotoxicity of deoxynivalenol, there are guidelines on the amount of this mycotoxin allowed in wheat in the United States and Canada (28).…”
Section: Introductionmentioning
confidence: 99%